Assessing Bias Introduced in Estimated Glomerular Filtration Rate by the Inhibition of Creatinine Tubular Secretion from Common Antiretrovirals. Issue 5 (July 2020) - Brunet, Laurence; Wyatt, Christina; Hsu, Ricky; Mounzer, Karam; Fusco, Jennifer; Fusco, Gregory
Background: Researchers must often rely on creatinine measurements to assess kidney function because direct glomerular filtration rates (GFR) and cystatin-c are rarely measured in routine clinical settings. However, HIV treatments often include dolutegravir, raltegravir, rilpivirine or cobicistat, which inhibit the proximal tubular secretion of creatinine without impairing kidney function, thus leading to measurement bias when using creatinine-based estimated GFR (eGFR). We developed eGFR correction factors to account for this potential bias. Methods: 11, 359 treatment-naive HIV-positive individuals in OPERA were included if they initiated dolutegravir, elvitegravir/cobicistat, darunavir/cobicistat, raltegravir, rilpivirine or efavirenz (control) with an eGFR >60 ml/min/1.73 m 2 . The eGFR was corrected by adding the median decrease reported in the literature to the calculated eGFR; correction factors were not validated. Incidence rates of eGFR <60 ml/min/1.73 m 2 (Poisson regression) and the relationship between regimens and eGFR <60 ml/min/1.73 m 2 (multivariate Cox proportional hazards models) were estimated with and without eGFR correction. Results: Without eGFR correction, dolutegravir, elvite-gravir/cobicistat, darunavir/cobicistat, raltegravir and rilpivirine based regimens were statistically significantly associated with a higher likelihood of eGFR <60 ml/min/1.73 m 2 than efavirenz. With eGFR correction, each of these regimens was associated with a statistically significantly lower likelihood of eGFR <60 ml/min/1.73 m 2 compared with efavirenz. Conclusions: With increasing use of agents that inhibit tubular creatinine secretion, artificially low eGFR values could lead to erroneous conclusions in studies of HIV treatment and kidney outcomes measured with creatinine-based eGFR equations. Sensitivity analyses assessing the potential magnitude of bias arising from creatinine secretion inhibition should be performed.